2022
DOI: 10.1080/13675567.2022.2088708
|View full text |Cite
|
Sign up to set email alerts
|

Implications of COVID-19 on the US container port distribution system: import cargo routing by Walmart and Nike

Abstract: The purpose of this paper is to discuss the implications of COVID-19 on container import flows via the US port distribution system. We employ statistics collected for more than 21 US ports and for more than 550 000 container shipments by Walmart and Nike to identify trends and potential shifts in the US port distribution system. Results unveil different changes in distribution channels during the pandemic era, between aggregated port level and industry level. These differences are specific to firms and could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…In our study, both disruptions had long durations and thus needed long-term flexibility. That result aligns with Cariou and Notteboom (2022) finding that whilst supply chain disruptions in the United States of America due to natural disasters (e.g. hurricanes) resulted in limited possibilities to substitute ports, the longer disruption of the COVID-19 pandemic involved lockdowns and slowdowns at major ports.…”
Section: Flexibility Considering Various Characteristics Of Disruptionssupporting
confidence: 83%
“…In our study, both disruptions had long durations and thus needed long-term flexibility. That result aligns with Cariou and Notteboom (2022) finding that whilst supply chain disruptions in the United States of America due to natural disasters (e.g. hurricanes) resulted in limited possibilities to substitute ports, the longer disruption of the COVID-19 pandemic involved lockdowns and slowdowns at major ports.…”
Section: Flexibility Considering Various Characteristics Of Disruptionssupporting
confidence: 83%
“…However, with the emergence of the Suez crisis, there has been significant motivation for Asian-sourced cargoes, bound for ECNA destinations, to utilize transpacific routings to access land-bridge rail services from US West Coast ports. A lateral impact of this trend would be the revival of WCNA port throughputs, which have been losing out constantly to ECNA ports (Kent and Haralambides 2022;Cariou and Notteboom 2023).…”
Section: Freight Rates and Surchargesmentioning
confidence: 99%
“…However, it is important to note that this time, the possibility of reintroducing lower prices to facilitate the quick recovery of the national and global trade is not an option [25]. Cariou and Notteboom analyzed the effects of the pandemic on the import container shipping routes and on the example of the port system in the United States [26]. During the research, the authors observed more than half a million of shipments by Nike and Walmart sent via container ships to the ports in the USA.…”
Section: Overview Of the Literature On The Maritime Container Industr...mentioning
confidence: 99%
“…During the research, the authors observed more than half a million of shipments by Nike and Walmart sent via container ships to the ports in the USA. The ability of adjusting the supply chain to the strong disruption was determined by the choice of the location for the production facilities, the transport company and the capillarity of the distribution network via the port system [26].…”
Section: Overview Of the Literature On The Maritime Container Industr...mentioning
confidence: 99%